The false click beetles (Coleoptera: Eucnemidae) of Hawai’i - Otto, Robert L. (Zootaxa, 2017)
The Hawaiian eucnemid fauna is reviewed. Each of the known species is redescribed along with descriptions of 20 new species. An overview of the distribution as well as any known aspects of natural history are provided for each species, and keys to identify the Hawaiian species are provided. The following 20 new taxa are described: Fornax muonai new species (type locality Hawai’i), Fornax swezeyi new species (Maui), Fornax yoshimotoi new species (Kaua’i), Dromaeolus acaciakoa new species (Kaua’i), Dromaeolus breviangularis new species (Kaua’i), Dromaeolus forbesi new species (Kaua’i), Dromaeolus halehakuensis new species (Maui), Dromaeolus hardyi new species (Maui), Dromaeolus harryi new species (Kaua’i), Dromaeolus kokeensis new species (Kaua’i) Dromaeolus leroyi new species (Kaua’i), Dromaeolus nualoloensis new species (Kaua’i), Dromaeolus oahuensis new species (O’ahu), Dromaeolus paulayi new species (Kaua’i), Dromaeolus ruffini new species (Hawai’i), Dromaeolus sandrae new species (Maui), Dromaeolus susanae new species (Kaua’i), Dromaeolus waikapuensis new species (Maui), Dromaeolus youngi new species (Kaua’i) and Dromaeolus zimmermani new species (Kaua’i). Dromaeolus pachyderes var. kauaiensis Sharp is elevated to D. kauaiensis Sharp, new status. Each species is illustrated with a dorsal habitus image and accompanied by a distribution map.